2018
DOI: 10.3126/jucms.v4i1.19075
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection In Laparotomy

Abstract: INTRODUCTION: Surgical site infection (ssi) is one of the most common surgical complications which increases the rate of morbidity and mortality and increases the health care cost by prolonging the hospital stay.  AIMS AND OBJECTIVES: The main objective of the study was to find out the incidence of ssi in emergency laparotomy in general surgery and to find out the associated risk factor for ssi.MATERIAL & METHODS: Study was carried out in national medical college, Birgunj from January 2011 to June 2012 aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Studies have shown that there is a significant association between the incidence of SSI and CDC class III or IV surgical wounds [4,7]. Important factors responsible for causing these are the presence of infected interstitial fluid in the wound bed, poor nutritional status, and immunocompromised state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that there is a significant association between the incidence of SSI and CDC class III or IV surgical wounds [4,7]. Important factors responsible for causing these are the presence of infected interstitial fluid in the wound bed, poor nutritional status, and immunocompromised state.…”
Section: Discussionmentioning
confidence: 99%
“…Class IV refers to traumatic wounds with devitalized tissue wherein the organism responsible for infection is present in the field pre-operatively [3]. The risk of postoperative SSI in Class III and IV surgical wounds is around 30-35% and 40-50%, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation